Multitier of Greenhouse Effect (MoGE) Instrument Development to Identify Middle School Students’ Mental Model in Thailand with Rasch Analysis - et al., Vianni Ismi Kania (International Journal of Advanced Science and Technology, 2020)
This research aims to develop of Multitier of Greenhouse Effect (MoGE) instrument to identify middle school students’ mental models in Thailand with Rasch Analysis. The research method used is 3D + 1I (Defining, Designing, Developing, & Implementing). Participants involved in this research were 33 students (average age 13-14 years) at one of Middle School in Khon Kaen, Thailand. The MOGE instrument consists of 10 items that have been analyzed using the Rasch model. The results showed that there were 5 categories of learners’ mental model profiles for students: 1) The Synthesis-Partial Understanding B category had the largest percentage of 47.47% in the greenhouse effect process indicator; 2) Synthesis-Partial Understanding A category with a percentage of 31.3% in the indicator of the type of greenhouse gas; 3) Initial category with a percentage of 31.3% on the greenhouse effect process indicator; 4 The category of misconception in the greenhouse effect process indicator with a percentage of 11.13%, and; 5) Scientific category with a percentage of 15.18% indicators of the causes and effects of the greenhouse effect, and measures to reduce the greenhouse effect.